Molecular Diversity Analysis of Jattal and Dera Din Panah Goat Breeds of Pakistan using Microsatellite Markers - HUSSAIN, T.; SHAHEEN, M.; BABAR, M. E.; MUSTHAFA, M. M.; NADEEM, A.; NAWAZ, A.; JAVED, M. M.; MARIKAR, F. (Journal of the Hellenic Veterinary Medical Society, 2018)
This paper evaluates the genetic diversity of goat breeds in Pakistan, a country blessed with a wide range of goats spread throughout with distinct features contributing to a rich Animal Genetic Resource. The genetic diversity of two goat breeds (Jattal and Dera Din Panah) was assessed with 25 animals representing the two breeds using 16 microsatellite markers. The mean observed and expected heterozygosity of both goat breed populations were observed as 0.83+0.21. The average number of observed alleles was 3.6+1.6 for all loci. The mean polymorphic information content for a goat breed was 0.45, indicating the usefulness of markers panel. Highest Nei’s standard genetic distance (Ds) value of 0.0612 was observed between Jattal and Dera Din Panah goats, and the mean Fst value was 0.013. The measures of genetic variation revealed a good scope for effective improvement, conservation, and designing national breeding policies, in future, for Pakistan goat breeds.